Evidence of verocytotoxigenic Escherichia coli (VTEC) in livestock of Tamil Nadu-an explorative study - Gopinathan, R; Kang, Gagndeep; V, Asokan G; N, Arunagirinathan; Vasanthana, George (The Indian Journal of Animal Sciences, 2005)
There is a paucity of data about the prevalence, burden of disease and complications associated with verocytotoxigenic Escherichia coli (VTEC) in animals in India. Cattle and other livestock harbour VTEC strains associated with haemorrhagic colitis (HC) and haemorrhagic ureamic syndrome (HUS). Therefore this explorative study analysed 115 livestock including healthy and diarrhoic animals for the excretion of VTEC. Isolates (12) belonging to non-sorbitol fermenting Escherichia coli (10.4%) were obtained out of 115 samples screened to tellurite cefixime-sorbitol MacConkey agar (TC-SMAC) that produced CPE on verocell monolayer. Culture filtrate of 4 out of these 12 E. coli isolates extracted after treatment with 10% (wlv) polymyxin B showed neutralization with antishigatoxin-1 suggesting them to be true VTEC strains. This study marks the first evidence of the isolation of VTEC from livestock in Tamil Nadu and underscores the need for large-scale epidemiological and bacteriological investigation to discern the mode of transmission and prevalent serotypes of VTEC in India.